Entrepreneurial Refugees and the City: Brief Encounters in Beirut. (1st February 2018) - Harb, Mona; Kassem, Ali; Najdi, Watfa
Abstract: Lebanon is hosting more than 1 million Syrian refugees. For a country of its size, and a population of around 4 million, this influx of Syrians into Lebanon has exposed many of its already established ailments. A prevailing perception is that Syrians are establishing businesses and competing with the Lebanese, leading to violent reactions on the part of host communities. In this article, we seek to debunk the reductionist framing of 'the Syrian refugee' as a burden, and showcase the economic contribution that some Syrian entrepreneurs have been making to urban neighbourhoods. While entrepreneurs certainly represent a minority of the refugees in Lebanon, we argue that, rather than being competition, Syrian entrepreneurs are complementary to Lebanese businesses in urban areas, and that Syrian businesses are enriching spatial practices in the city. As such, we claim their experiences are significant to document as they can inform useful policy interventions that can render Syrian self-employment an opportunity for local economic development in cities and towns.